OPTIMALISASI PERAN DAKWAH ULAMA DALAM MENSOSIALISASIKAN PENCEGAHAN PERNIKAHAN DINI DI NUSA TENGGARA BARAT - Sigit Sigit; Ahmad Nurcholis (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2023)
In enssence, da’wah is inviting oneself and others to believe in Allah His Messenger. Not only Islam, other religions teach same thing to call for foofness according to their respective teachings and beliefs. The essence of the teachings of Islam itself is amar ma’ruf nahi munkar. Historical facts say that Islam has experienced success in spreading His holy teachings through His messenger Prophet Muhammad Saw. This success cannot be separated from the da’wah method carriend out by him, one of which uses the bil-qolam dakwah method (writing or pen). The research method uses qualitative research with a literature review approach and analysis of the phenomenom of da’wah. The results of this study answer about a) the comparison of the bilqolam da’wah of the Prophet Muhammad with da’wah in the modern era b) the implemetation of the bil-qolam da’wah of the Prophet Muhammad on the comsumpritive of modern society.